(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2010)
The article is devoted to the comparative analysis of phraseological units with zoo component which express moral qualities of people in the English and Ukrainian languages. Special attention is paid to the negative or positive estimation, which is the basis of the connotation of the phraseological unit.